Emerging single port laparoscopic colorectal surgery - Mittermair, Christof; Weiss, Michael; Weiss, Helmut G.; ECSPECT Study group, on behalf of the (Annals of Laparoscopic and Endoscopic Surgery, 2017)
We read with great interest the Editorial “Single port laparoscopic colorectal surgery: what did we learn from the ECSPECT prospective multicenter registry study?” by Marks and Nagatomo (1).